JUSTIFICATION OF THE DESIGN OF A 3D PRINTER EXTRUDER NOZZLE USING GRANULES AND CUT POLYMER PARTICLES AS INPUTS - POLISHCHUK, ANDRII; SKYBA, MYKOLA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article defines extrusion as a continuous process of converting a solid bulk polymer into a viscous state followed by pushing it through a molding tool. It is emphasized that extruders are one of the most promising types of equipment for processing polymer materials and are used in various industries, including 3D printing. Attention is focused on the fact that one of the important parts of each extrusion unit is the extrusion head. It is the main tool that determines the final shape of extruded products. It is emphasized that the extruder nozzle has a significant impact on the quality of 3D printing. Four parameters characterizing the nozzle are highlighted: its external size, internal structure, diameter of the hole for extruding the polymer, and the material from which it is made, and each is considered in detail. The main physical and mechanical properties of nozzles made of different materials are presented. A classification of nozzles was developed on the basis of the conducted review. The formula for determining the volumetric productivity of a 3D printer extruder is given, depending on the design of its dosing zone and nozzle resistance. An expression for determining the total resistance coefficient of the nozzle is given, which is defined as the sum of the resistance coefficients of individual geometrically simple sections of its internal structure. It is proposed to use in the extruder of a 3D printer that uses granules or crushed polymer particles as raw materials for the construction of nozzles for 3D printers that print with filament. With their use, a new nozzle design for screw extruders was developed and presented. Based on the analysis of the internal structure of nozzles for 3D printers that print with filament and forming devices of plastic processing equipment, the design of the extruder nozzle using a mandrel was developed and presented.